2017
DOI: 10.1111/jns.12194
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of complement in Guillain‐Barré syndrome: the ICA‐GBS study

Abstract: The outcome of Guillain-Barré syndrome (GBS) remains unchanged since plasma exchange and intravenous immunoglobulin (IVIg) were introduced over 20 years ago. Pathogenesis studies on GBS have identified the terminal component of complement cascade as a key disease mediator and therapeutic target. We report the first use of terminal complement pathway inhibition with eculizumab in humans with GBS. In a randomised, double-blind, placebo-controlled trial, 28 subjects eligible on the basis of GBS disability grade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 24 publications
(22 reference statements)
0
37
0
Order By: Relevance
“…In addition, development of new therapeutic options, such as complement inhibition, may be needed for patients with poor prognosis. This issue is now under investigation (Yamaguchi et al, ; Davidson et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, development of new therapeutic options, such as complement inhibition, may be needed for patients with poor prognosis. This issue is now under investigation (Yamaguchi et al, ; Davidson et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients who had died or were lost to follow-up in the first 7 days from study entry, or who received a second IVIg course because of a reported treatment related fluctuation (TRF) observed by the local physician 13. We also excluded patients who participated in a randomised controlled study (Second Immunoglobulin Dose in GBS patients (SID-GBS) trial14 15 or Inhibition of Complement Activation in GBS (ICA-GBS) trial) 16…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, we need to translate increased understanding of pathogenesis to meaningful treatment or prevention. Immunotherapeutic trials of blocking the complement cascade (ie, eculizumab, 88,89 monoclonal antibodies binding to complement factor 5) are under way.…”
Section: Precautionsmentioning
confidence: 99%